A discursive analysis of what sexual violence perpetrators say to their victims - Coopoo, Perishka (Rhodes University, Faculty of Humanities, Department of Psychology, 2017)
This research study aimed to examine the way in which sexual violence perpetrators talk to their victims by critically investigating the discursive strategies drawn on by perpetrators, the discursive constructions of their actions and their victims, and the consistencies with the talk of sexual violence perpetrators and rape myths and discursive and social practices promoting sexual violence. Over two-hundred photographs were collected from a photographic art project called Project Unbreakable. The photographs were of sexual violence survivors, from all over the world, holding a poster with a quote from their attacker. The words that survivors chose to represent for Project Unbreakable served as the data for this research study. The data were analyzed using the six stages of Foucauldian discourse analysis outlined by Carla Willig. The analysis revealed that by drawing on discourses of pleasure, desire, romance, marriage and consent, perpetrators discursively constructed their actions as sex. Furthermore, perpetrators discursively constructed their victims as sexually passive and dependant on men, as gate keepers of men's sexuality, as sexual instruments for male satisfaction, and as consenting persons. On the other hand, perpetrators were also found to discursively construct their actions as a legitimized form of punishment, humiliation and intimidation. In addition, their victims were discursively constructed as deviant, deserving of their victimization, worthless, damaged and powerless. These discursive constructions of their actions and their victims enabled perpetrators to normalize their behaviour, blame their victims, minimize the incident, assert their innocence, justify their actions, silence their victims and reinforce their position at the top of the gender hierarchy. Consistencies were also found between the talk of perpetrators and rape myths, stereotypes and discursive and social practices promoting sexual violence. Another interesting finding in the data was that of quotes from a third party, not the perpetrator, which further illustrated the existence of rape culture. This research draws on the idea that a rape supportive culture does not only capture the hostile nature of the social environment that many survivors experience in the aftermath of sexual violence, but it also provides a social pattern for coercive sexuality to occur.
Keywords: Project Unbreakable; Rapists -- Language; Rape -- Social aspects; Language and sex; Sexual harassment of women; Women -- Crimes against; Discoure analysis